The Effect of Working Capital Turnover and Profitability of Inventory Turnover Manufacturing Companies Listed in Indonesia Stock Exchange - Seto Sulaksono Adi Wibowo; Eni Rohyati (Journal of Applied Accounting and Taxation, 2018)
This research is to explain the relationship working capital turnover and inventory turnover on the level of profitability of manufacturing as well as how big the effect of working capital turnover and inventory turnover on the profitability of company. The effect the relationship between working capital turnover and inventory turnover on profitability (ROA) companies. Sample collection technique using purposive sampling method. Analysis of data using multiple linear regression. This study with multiple tested with multiple regression analysis , t-test, and test the coefficient of determination. Data used in this research is secondary data bay using the financial statement in the Indonesia Stock Exchange on 30 sample of company manufacturing period 2012-2014. The result of this study and discussion, it can be concluded that the working capital turnover indicator negative influence on profitability while inventory turnover indicator positive effect on profitability of the company manufacturing 2012-2014 period.